2020
DOI: 10.1002/ece3.6281
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for senescence in survival but not in reproduction in a short‐lived passerine

Abstract: Senescence has been studied since a long time by theoreticians in ecology and evolution, but empirical support in natural population has only recently been accumulating. One of the current challenges is the investigation of senescence of multiple fitness components and the study of differences between sexes. Until now, studies have been more frequently conducted on females than on males and rather in long‐lived than in short‐lived species. To reach a more fundamental understanding of the evolution of senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Owing to the natural stochasticity of these factors and potentially the lack of alternative nesting sites, it might be difficult for pied flycatchers to find nesting sites in the first place and assess nesting site safety at settlement and thus to control nest success. In small passerines, the stochasticity in nest success can be an important process to mask potential age effects in fecundity (Fay et al 2020b;Mitrus 2004 but see Horie and Takagi 2012;Robertson and Rendell 2001;Pärt 2001). This contrasts with long-lived species for which nest success is more frequently associated with age (Berman et al 2009;Froy et al 2017;Murgatroyd et al 2018;Newton et al 1981).…”
Section: Reproductive Aging and Synchronymentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the natural stochasticity of these factors and potentially the lack of alternative nesting sites, it might be difficult for pied flycatchers to find nesting sites in the first place and assess nesting site safety at settlement and thus to control nest success. In small passerines, the stochasticity in nest success can be an important process to mask potential age effects in fecundity (Fay et al 2020b;Mitrus 2004 but see Horie and Takagi 2012;Robertson and Rendell 2001;Pärt 2001). This contrasts with long-lived species for which nest success is more frequently associated with age (Berman et al 2009;Froy et al 2017;Murgatroyd et al 2018;Newton et al 1981).…”
Section: Reproductive Aging and Synchronymentioning
confidence: 99%
“…This contrasts with long-lived species for which nest success is more frequently associated with age (Berman et al 2009;Froy et al 2017;Murgatroyd et al 2018;Newton et al 1981). Because breeding failure is a key component of breeding performance, nest success may affect the overall relationship between age and fecundity (Fay et al 2020b). Thus, more studies are needed to seek for generality in the critical relationship between nest success and age, especially in short-lived species.…”
Section: Reproductive Aging and Synchronymentioning
confidence: 99%
“…It could be because within adult group, we include birds of several years, older birds, with a shorter life expectancy. That is, we are putting the effect of senescence in survival estimates (Fay et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although birds and mammals show similar age-related decline and pathology (Holmes and Ottinger, 2003), their reproductive senescence seems to differ. For example, in the short-lived whinchat, virtually no sign of reproductive senescence could be identified until the age of 4 years, although survival started to decline at an age of only 1 year (Fay et al, 2020). Furthermore, in contrast to mammals, female birds display similar or partially even shorter life expectancies than males (Orell and Belda, 2002;Fay et al, 2020).…”
Section: Birds Birds (Aves)mentioning
confidence: 99%
“…For example, in the short-lived whinchat, virtually no sign of reproductive senescence could be identified until the age of 4 years, although survival started to decline at an age of only 1 year (Fay et al, 2020). Furthermore, in contrast to mammals, female birds display similar or partially even shorter life expectancies than males (Orell and Belda, 2002;Fay et al, 2020). In a comprehensive study including 339 bird species, it was demonstrated that brain size, independently from body mass, correlates with longevity (Jiménez-Ortega et al, 2020).…”
Section: Birds Birds (Aves)mentioning
confidence: 99%